اسلامی نسائیت،تعبیر نو کاجدید نسائی بیانیہ:ایک تحقیقی جائزہ - Ambreen Ali (Pakistan Journal of Islamic Research)
Feminism, a global movement which advocates for the rights of Women has evolved in different forms from its origin in the Western societies. It has been challenged and modified from variety of perspectives such as thoughts, culture, class and regions. The global debate on the position of women in Muslim society, which has been largely initiated by the current wave of Islamic revivalism. Muslims and non-Muslims, Islamists and opponents of Islamism, and feminists are playing key role in it.Muslims generally argue that there is an ideal gender prototype in Islam, non-Muslims tend to disagree and emphasize that Islam is hostile to women. Therefore, this paper analyzes the feminist movement in Islam by delving into its origin, development and diversities within the Islamic thought. It explores the new development of feminist notions within the Islamic framework, namely “Islamic feminism “. In the intellectual and academic debate of the 1990s, the expression “Islamic feminism “was used in a number of different places around the globe. Islamic feminism is diverse and varied in its approach to the issue of claiming the rights of Muslim women. This school of thought emphasized the right to engage in interpretation (ijtihad) that promoted gender equality, new roles for women in religious ritual and practice. Islamic feminism is a highly contested term but it has also been widely embraced by both feminist activists and Muslim scholars. Thus, this articles aims to explain the diversity in the discourse of Islamic feminism.it also provides the comprehensive views of western and Muslim scholars.